THE IMPACT OF DIGITALIZATION ON REDUCING CORRUPTION IN THE ECONOMY - Rakhmatjanov Lazizkhan Turabayevich, (Ta'lim innovatsiyasi va integratsiyasi, 2026)
Abstract: Modern society is facing one of the most serious social problems – the spread of corruption in all spheres of the economy. Moreover, this problem requires a  comprehensive  and  systematic  approach  to  overcome  it,  including  the  active participation of the state, organizations and citizens. The state's anti-corruption policy is  actively  developing  and  increasingly  intersects  with  the  development  of  digital technologies. Publications devoted to the prevention of corruption usually focus on the analysis  of  a  system  of  measures  aimed  at  preventing,  detecting  and  eliminating corruption. This study is devoted to the use of such a tool in the fight against corruption as  digitalization.  Digitalization  in  the  activities  of  public  authorities  is  a  complex process that involves a number of problems that need to be resolved, some of which are discussed in this paper. The use of modern digital technologies and the practice of electronic public administration are one of the effective tools of anti-corruption policy in the digital space. Today, the development, adoption and implementation of modern legislative frameworks for the introduction and application of innovative digital anti-corruption technologies seem relevant.